[Rezension von: Ueno Takafumi (Hrsg.), Coordination chemistry in protein cages] - Krämer, Roland (Angewandte Chemie. International edition, 2014)
John Wiley and Sons, Hoboken, 2013. 416 pp., hardcover, € 89.99.—ISBN 978-1118078570
Gesehen am 14.01.2021
Keywords: Rezension